2021
DOI: 10.48550/arxiv.2107.10374
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generation of a maximally entangled state using collective optical pumping

M. Malinowski,
C. Zhang,
V. Negnevitsky
et al.

Abstract: We propose and implement a novel scheme for dissipatively pumping two qubits into a singlet Bell state. The method relies on a process of collective optical pumping to an excited level, to which all states apart from the singlet are coupled. We apply the method to deterministically entangle two trapped 40 Ca + ions with a fidelity of 93(1)%. We theoretically analyze the performance and error susceptibility of the scheme and find it to be insensitive to a large class of experimentally relevant noise sources.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…Our demonstration of dissipative singlet generation with fidelity of ∼0.95, along with the related work by Malinowski et al [24], is a step forward in dissipative produc-tion of entangled resource states. These works indicate a path towards fidelities that could allow productive incorporation of dissipative protocols into practical trappedion platforms for quantum information processing.…”
Section: States Involving ȁ ۧ Auxsupporting
confidence: 55%
See 1 more Smart Citation
“…Our demonstration of dissipative singlet generation with fidelity of ∼0.95, along with the related work by Malinowski et al [24], is a step forward in dissipative produc-tion of entangled resource states. These works indicate a path towards fidelities that could allow productive incorporation of dissipative protocols into practical trappedion platforms for quantum information processing.…”
Section: States Involving ȁ ۧ Auxsupporting
confidence: 55%
“…Recently, schemes have been proposed that avoid these timescale hierarchies. Instead, these schemes make more efficient use of experimental resources such as symmetries and auxiliary degrees of freedom [18][19][20][21]24], and are generally expected to produce the desired target state with higher fidelity in less time.…”
mentioning
confidence: 99%
“…Multimode squeezed states exhibit a large interest for QIP applications, such as quantum state sharing, quantum teleportation and multipartite entangled states [47,89,90,115,116]. It was recently demonstrated that the affine quantization of the cosmological dynamics removes the classical singularity and univocally establishes a unitary evolution.…”
Section: Late Results and Applicationsmentioning
confidence: 99%
“…We have recently used this capability to demonstrate a new scheme for dissipative steadystate entanglement of ions. 14 This used sequences of 16 gates and thus tested the performance in extended sequences. Charging of the chip due to high power light, and the high heating rates exhibited by the ions were primary limitations on both works, with the charging being especially problematic when running variable-length sequences, since the duty cycle of light delivery seems to affect the build-up of charge.…”
Section: Multi-qubit Gates Using Integrated Photonicsmentioning
confidence: 99%